PEMBENTUKAN MORALITAS SISWA - Tomas Sialana (Institut Agama Kristen Negeri (IAKN) Ambon, 2018)
Morality or morality is the doctrine of the Good, the bad that is generally accepted concerning deeds, attitudes, and obligations. SMP Negeri 6 Ambon is a school in the category of excellent schools but there are still students who have moral not good at communicating and behave with teachers and friends such as: like to remove the words of diatribe or in the local language Called Bamaki, the attitude and intonation of the voice of the students, in speaking with the teacher in the school is not polite, anyone uploading pornographic pictures of even pornographic videos, it is very bad impact on the moral and future of the students. The purpose of this writing is to know and give good understanding to the school, parents, church, to the moral reality of SMP Negeri 6 Ambon, and the importance of the role of teachers in schools, parents, and the church in shaping Good student moral. In this study using Rahmad's theory. This research uses a qualitative approach. And the method used in this research is qualitative. Morality or morality is the doctrine of the Good, the bad that is generally accepted concerning deeds, attitudes, and obligations. SMP Negeri 6 Ambon is a school in the category of excellent schools but there are still students who have moral not good at communicating and behave with teachers and friends such as: like to remove the words of diatribe or in the local language Called Bamaki, the attitude and intonation of the voice of the students, in speaking with the teacher in the school is not polite, anyone uploading pornographic pictures of even pornographic videos, it is very bad impact on the moral and future of the students. The purpose of this writing is to know and give good understanding to the school, parents, church, to the moral reality of SMP Negeri 6 Ambon, and the importance of the role of teachers in schools, parents, and the church in shaping Good student moral. In this study using Rahmad's theory. This research uses a qualitative approach. And the method used in this research is qualitative. From the research shows that, the establishment of student morality is an effort made by certain parties in shaping the moral of poor students into good moral. Another fact that the authors find is, that the school in the category (the Superior school) is not all students who are in the school institution, have good morality, that is in accordance with the vision and mission or purpose of the school institution. The morality of a good student can not be seen from the intelligence and achievements that the students have because, the savvy student is not necessarily moral either. Responsibility to form the moral of students is not only done by teachers, but parents, church and community also involved in carrying out his role. But the fact shows that parents, churches and communities are not maximized in carrying out their role in regards to the intended thing.Keyword: student morality